The role of FDI in structural change: Evidence from Mexico - Octavio Escobar; Henning Mühlen (Kiel Centre for Globalization (KCG), 2018)
Foreign direct investment (FDI) flows to Mexico are substantial and play an important role in the Mexican economy since the mid-1990s. These investments reflect the activities of multinational firms that shape to some extent the economic landscape and sectoral structure in this host country. We illustrate that there is considerable variation in the amounts of FDI and structural change within the country and across time. Based on this, the paper's main purpose is to analyze whether there is a significant impact of FDI on structural change. We conduct an empirical analysis covering the period 2006-2016. We use the fixed-effects estimator where the unit of observation is a Mexican state for which we calculate structural change from the reallocation of labor between sectors. The results suggest that (if any) there is a positive effect from FDI on growth-enhancing structural change. This effect depends critically on the lag structure of FDI. Moreover, there is some evidence that the positive effect (i) arises from FDI flows in the industry sector and (ii) is present for medium- and low-skilled labor reallocation.
Keywords: F21; F63; L16; O10; O54; 330; FDI; structural change; labor reallocation; Mexico; multinational firms; economic development